No injuries, but plenty of pain? On the methodology for recording overuse symptoms in sports - Bahr, R. (British Journal of Sports Medicine, 2009)
Overuse injuries may represent as much of a problem as do acute injuries in many sports. This paper reviews key concepts related to the methodology for recording overuse symptoms. Results from the FIVB Volleyball Injury Study were used to compare two different recording methods. The aim of this paper was to provide recommendations on how standardised methodology can be developed to quantify overuse injuries in surveillance studies. Using beach volleyball data, a "traditional" cohort study approach using a time-loss injury definition suggested that injury risk was very low. In contrast, the data from a survey of past and present pain problems in the shoulder, knees and low back demonstrated that these were prevalent. The following recommendations are made: (1) studies should be prospective, with continuous or serial measurements of symptoms; (2) valid and sensitive scoring instruments need to be developed to measure pain and other relevant symptoms; (3) prevalence and not incidence should be used to report injury risk; (4) severity should be measured based on functional level and not time loss from sports. In conclusion, new approaches are needed to develop more appropriate methodology to quantify overuse injuries in studies.